2004
DOI: 10.1016/j.imlet.2003.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of complement-induced cell lysis: a novel mechanism for the anticancer effects of Hsp90 inhibitors

Abstract: Molecular chaperones (heat shock proteins, Hsp-s) play a pleiotropic role in immunological functions. Hsp-s participate in the presentation of peptide antigens, folding of several immunologically important proteins, such as the MHC, and in the maintenance of the activation-competent conformation of key signaling molecules (mostly serine/threonine and tyrosine kinases) of B and T cells activation. The most abundant cytoplasmic chaperone, Hsp90, is in the center of these processes. In recent years Hsp90 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It influences the activity of many client proteins that function as critical regulators of cellular growth, differentiation, and apoptotic pathways (15). Hsp90 client proteins include oncogenic proteins in human malignancies acting via multiple signal transduction pathways: steroid receptors, epidermal growth factor receptor family members, MET, Raf-1 kinase, AKT, Bcr-abl, mutant p53, CDK4, and many other molecules (6–8).…”
mentioning
confidence: 99%
“…It influences the activity of many client proteins that function as critical regulators of cellular growth, differentiation, and apoptotic pathways (15). Hsp90 client proteins include oncogenic proteins in human malignancies acting via multiple signal transduction pathways: steroid receptors, epidermal growth factor receptor family members, MET, Raf-1 kinase, AKT, Bcr-abl, mutant p53, CDK4, and many other molecules (6–8).…”
mentioning
confidence: 99%
“…Studies involving experimental exposure to electromagnetic fields have revealed numerous modifications in the expression of heat shock proteins in vivo [8] and in vitro, in cell lines [9]. HSP-90 is the most common type of heat shock protein [10] and occurs at higher levels in nerve tissues than in non nerve tissues [11] and is distributed in neurons in the limbic system, neocortex, striatus and thalamus [12,13]. This protein acts to regulate the activity of other proteins such as steroid hormone receptors [14] kinase [15], calmodulin [16], actin [17], and tubulin [18].…”
Section: Introductionmentioning
confidence: 99%
“…5 HSPs play a pivotal role in protecting cells from apoptosis, thereby prolonging survival. [3][4][5][6][7] In recent years, the molecular chaperone that has emerged as the most promising target of innovative cancer therapy is HSP90. HSP90 is ubiquitously expressed in the cytoplasm of normal cells where it binds with many client proteins and is involved in homeostasis.…”
mentioning
confidence: 99%
“…HSP90 is ubiquitously expressed in the cytoplasm of normal cells where it binds with many client proteins and is involved in homeostasis. [1][2][3][4][5][6][7] In normal cells, HSP90 is expressed at relatively low levels and does not form complexes with other chaperone proteins. 8 Thus, others have suggested that HSP90 is present in latent form in normal cells.…”
mentioning
confidence: 99%